2004
DOI: 10.3346/jkms.2004.19.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Meropenem for Treatment of Experimental Penicillin-Resistant Pneumococcal Meningitis

Abstract: With the widespread emergence of antimicrobial resistance, combination regimens of ceftriaxone and vancomycin (C+V) or ceftriaxone and rifampin (C+R) are recommended for empirical treatment of pneumococcal meningitis. To evaluate the therapeutic efficacy of meropenem (M), we compared various treatment regimens in arabbit model of meningitis caused by penicillin-resistant Streptococcus pneumoniae (PRSP). Therapeutic efficacy was also evaluated by the final bacterial concentration in the cerebrospinal fluid (CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
1
0
2
Order By: Relevance
“…Assim, o meropenem é considerado mais seguro, quando comparado ao imipenem, pelo menor potencial convulsivo. Em Medicina Veterinária, há um estudo utilizando meropenem, associado à vancomicina em coelhos, como terapia eficaz para meningite causada por Streptococcus pneumoniae resistente à penicilina [7]. Não há estudos que comprovem a segurança de carbapenêmicos em gatos, definição de dose terapêutica padronizada, bem como relatos de caso que associem hemólise a sua utilização.…”
Section: Discussionunclassified
“…Assim, o meropenem é considerado mais seguro, quando comparado ao imipenem, pelo menor potencial convulsivo. Em Medicina Veterinária, há um estudo utilizando meropenem, associado à vancomicina em coelhos, como terapia eficaz para meningite causada por Streptococcus pneumoniae resistente à penicilina [7]. Não há estudos que comprovem a segurança de carbapenêmicos em gatos, definição de dose terapêutica padronizada, bem como relatos de caso que associem hemólise a sua utilização.…”
Section: Discussionunclassified
“…In cases of meningitis caused by rifampin-susceptible strain, the combination of ceftriaxone and rifampin showed a much higher bactericidal activity than that of ceftriaxone and vancomycin or meropenem plus vancomycin [ 23 ]. Animal models of meningitis have demonstrated activity of rifampin paired with one of these agents, even with cephalosporin-resistant organisms [ 24 ]. Therefore, it is suggested that rifampin should be used in combination if the organism is susceptible to rifampin or if there is a delay in the treatment response to regimens without rifampin [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…El meropenem es una opción que se ha demostrado eficaz en un ensayo clínico 99 , pero en un modelo experimental de meningitis por S. pneumoniae resistente a penicilina, meropenem se mostró inferior a ceftriaxona más vancomicina 100 . No obstante, el panel cree que, al ser un carbapenem de amplio espectro, no debe emplearse en primera línea ya que existen otras opciones de espectro más reducido.…”
Section: Tratamiento Dirigido De Infección Por S Pneumoniaeunclassified